2020
DOI: 10.1163/9789004440494
|View full text |Cite
|
Sign up to set email alerts
|

Drug Policies and Development

Abstract: Koninklijke Brill NV reserves the right to protect the publication against unauthorized use and to authorize dissemination by means of offprints, legitimate photocopies, microform editions, reprints, translations, and secondary information sources, such as abstracting and indexing services including databases. Requests for commercial re-use, use of parts of the publication, and/ or translations must be addressed to Koninklijke Brill NV. This book is printed on acid-free paper and produced in a sustainable mann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 100 publications
(123 reference statements)
0
2
0
Order By: Relevance
“…Naturally, this article is now well-suited to assume the mission of confirming the separation of things from objects in the ANT-based reality of opium addiction history by taking into consideration the theory of interaction and moral externalism (Chen 2022). In essence, the current opiate historiography dictates that our memories about the narcotic have been the end product of a series of reactions in which non-mystical facts of opium interacted with humanity's drug-centered psychologies to generate "chemistries" for the existential occurrences of opioid prohibitions in the historical realm (see Buxton et al 2020). By deduction, without the complement of "opiate substantiality," a mere writing of the drug's humanized influences impairs the full portrayal of a realist past for substance addictions.…”
Section: The Separation Of Things From Objects In Ant By Realist Phil...mentioning
confidence: 99%
“…Naturally, this article is now well-suited to assume the mission of confirming the separation of things from objects in the ANT-based reality of opium addiction history by taking into consideration the theory of interaction and moral externalism (Chen 2022). In essence, the current opiate historiography dictates that our memories about the narcotic have been the end product of a series of reactions in which non-mystical facts of opium interacted with humanity's drug-centered psychologies to generate "chemistries" for the existential occurrences of opioid prohibitions in the historical realm (see Buxton et al 2020). By deduction, without the complement of "opiate substantiality," a mere writing of the drug's humanized influences impairs the full portrayal of a realist past for substance addictions.…”
Section: The Separation Of Things From Objects In Ant By Realist Phil...mentioning
confidence: 99%
“…Other studies have shown that alternative development programs have not been successful in reducing illicit crop cultivation (Buxton 2015) 2 and have increased violence against target populations (Marín Llanes 2022). Mainly because the focus has been short-term (Lupu 2004), in small territorial spaces (Vargas 2011), and has been integrated into the security agenda, instead of to a broader development policy (Garzón & Gélvez 2018).…”
Section: Introductionmentioning
confidence: 99%